2019
DOI: 10.1101/584607
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Environmental interactions with amoebae as drivers of bacterial-fungal endosymbiosis and pathogenicity

Abstract: Environmentally ubiquitous fungal spores of the Mucorales order cause acute invasive infections through germination and evasion of the mammalian host immune system. Early phagocyte control of spore germination plays a key role in controlling infection, yet swelling Mucorales spores evade phagocytosis through an unknown mechanism. Here we investigate fungal immune evasion in a clinical isolate of Rhizopus microsporus and reveal the role of a bacterial endosymbiont, Ralsonia pickettii, in fungal pathogenesis. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 124 publications
(256 reference statements)
1
9
0
Order By: Relevance
“…Both clinical and plant pathogenic isolates of Mucorales are known to harbor bacterial endosymbionts (Ibrahim et al, 2008). Some initial experiments suggested that the bacterial endosymbionts had no effect on the virulence potential of the fungus that they live inside of Ibrahim et al (2008) but recent work has set a precedent for a role in evasion of host innate immune cells (Itabanga et al, 2019). Specifically, Ralstonia pickettii promotes the ability of R. microsporus to survive killing by macrophages (Itabanga et al, 2019).…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both clinical and plant pathogenic isolates of Mucorales are known to harbor bacterial endosymbionts (Ibrahim et al, 2008). Some initial experiments suggested that the bacterial endosymbionts had no effect on the virulence potential of the fungus that they live inside of Ibrahim et al (2008) but recent work has set a precedent for a role in evasion of host innate immune cells (Itabanga et al, 2019). Specifically, Ralstonia pickettii promotes the ability of R. microsporus to survive killing by macrophages (Itabanga et al, 2019).…”
Section: Future Directionsmentioning
confidence: 99%
“…Some initial experiments suggested that the bacterial endosymbionts had no effect on the virulence potential of the fungus that they live inside of Ibrahim et al (2008) but recent work has set a precedent for a role in evasion of host innate immune cells ( Itabanga et al, 2019 ). Specifically, Ralstonia pickettii promotes the ability of R. microsporus to survive killing by macrophages ( Itabanga et al, 2019 ). In a transcriptome-focused companion paper, Sephton-Clark et al (2019) examined the transcriptional response of J774.1 macrophages following phagocytosis of R. delemar and R. microsporus either with or without their bacterial endosymbionts living inside them.…”
Section: Future Directionsmentioning
confidence: 99%
“…Paraburkholderia -related endobacteria (PRE) were discovered in Mucorales, Umbelopsidales, and Mortierellomycotina representatives ( Okrasińska et al, 2021 ). Lately, information about two other endosymbionts of Rhizopus microsporus has been published: Ralstonia pickettii as an facilitator of fungal invasion during infection ( Itabangi et al, 2019 ) and Stenotrophomonas sp. whose role has not yet been established ( Virgianti and Natalia, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Data obtained from various studies indicated that the species of R. microsporus found symbiosis with B. rhizoxina and B. endofungarium were derived from soil, rice seedlings, peanuts, Vietnamese Sufu starter, and tempeh (Lacker et al 2009;Rohm et al 2010;Dolatabadi et al 2016). A different genus of endosymbiont bacteria has been isolated from the clinical isolate of R. microsporus was identified as Ralstonia pickettii contributing to fungal stress resistance and immune cell evasion as part of fungal pathogenesis in animal models (Itabangi et al 2019). The aim of this study was to determine and identify endosymbiont bacteria in Rhizopus sp.…”
Section: Introductionmentioning
confidence: 99%